Public acceptance of policy measures to prevent and combat infectious diseases in pets: a systematic literature review - Wyler, Michelle Kim Emily (Frontiers in Veterinary Science, 2026)
Zoonotic diseases represent a critical and growing threat to global public health. While farm and wild animals are already heavily integrated into policy measures of disease prevention, companion animals do often not get included in the fight against zoonotic diseases, despite their proximity to humans. Nevertheless, policy measures focusing on household pets are a crucial element in the prevention and combat of infectious diseases. This systematic literature review, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, summarizes the research on pet-targeted disease prevention measures, focusing on factors influencing their acceptability. Factors influencing acceptance were categorized in an expanded Nodality-Authority-Treasure-Organization (NATO) scheme adapted from Hood. A total of 95 articles were included in the study and provide insights across thirty-two countries. Thereby, personal owners' characteristics emerge as the most frequently studied factor influencing acceptance. The review found information provision by veterinarians, affordability, organizational accessibility, and pet controllability to be the most influential factors affecting public acceptance. This review highlights that the interplay of policy decisions with factors of context must be considered in order to accelerate acceptance, and that successful implementation depends on integrating veterinary, social, and behavioral perspectives.